Utility of Bronchoscopy with Bronchoalveolar Lavage in Diagnosing Pulmonary Infection in Hospitalized Patients with Underlying Malignancy - CW Chow; A McGeer; G Kasupski; N Senathiragah; P Gallant; CK Chan (Canadian Journal of Infectious Diseases)
Objectives: To evaluate the clinical utility of bronchoscopy with bronchoalveolar lavage (BAL) for diagnosing pulmonary infection in patients with underlying malignancy and to evaluate the impact of positive microbiology results on antimicrobial therapy.